Analisis flypaper effect berdasarkan kemampuan keuangan daerah - Lasmi Mutia; Fitriadi Fitriadi; Muliadi Muliadi (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
This  study  aimed  to  analyzed  the  local  financial  capacity  Kutai  Kartanegara  regency suspected of having flypaper effect. Types of the data from this research is quantitative. The types of the data in this research is in the form of time series data reports on realization of local revenue (PAD), equalization funds, regional expenditures and the amount of revenue Kutai Kartanegara Regency using quantitative analysis methods. Using the methods of analysis of financial index capability ratio (ICR) and analysis of the degree of fiscal decentralization. The results of the analysis in this research shows that the first analysis of the index calculation financial capability ratio Kutai Kartanegara Regency in the last  three  years shows  the indicator  is  very low  and  can  be said  to  experience the phenomenon flypaper effect and the second analysis, the calculation of the degree of fiscal decentralization Kutai Kartanegara Regency show the indicator is very less, This implies Kutai Kartanegara Regency government is still unable to finance its own expenses and still dependent on central government funding.